The Protective Effect of E. faecium on S. typhimurium Infection Induced Damage to Intestinal Mucosa - Zhang, Hang; Wang, Minjuan; Jia, Junpeng; Zhao, Jiayi; Radebe, Stoffel Matjeke; Yu, Qinghua (Frontiers in Veterinary Science, 2021)
Intensive farming is prone to induce large-scale outbreaks of infectious diseases, with increasing use of antibiotics, which deviate from the demand of organic farming. The high mortality rate of chickens infected with Salmonella caused huge economic losses, the promising safe prevention and treatment measures of Salmonella are in urgent need, such as probiotics. Probiotics are becoming an ideal alternative treatment option besides antibiotics, but the effective chicken probiotics stains with clear protective mechanism against Salmonella remains unclear. In this study, we found Enterococcus faecium YQH2 was effective in preventing Salmonella typhimurium infection in chickens. Salmonella typhimurium induced the loss of body weight, liver and intestinal morphology damage. The inflammatory factors levels increased and intestinal proliferation inhibited. However, after treatment with Enterococcus faecium YQH2, broilers grew normally, the pathological changes of liver and intestine were reduced, and the colonization of Salmonella in the intestine was improved. Not only that, the length of villi and the depth of crypts were relatively normal, and the levels of inflammatory factors such as IL-1β, TNF-α, and IL-8 were reduced. The number of PCNA cells of Enterococcus faecium YQH2 returned to normal under the action of Salmonella typhimurium infection, which was conducive to the normal proliferation of intestinal epithelial cells. The protective effect of Enterococcus faecium YQH2 may be due to the attribution to the activation of hypoxia and then induced the proliferation of intestinal stem cells to repair the damage of intestinal mucosa under Salmonella typhimurium infection. This study demonstrated that Enterococcus faecium YQH2 was effective in preventing Salmonella typhimurium infection, which could be further used in the chicken health breeding.